2016
DOI: 10.3354/aei00162
|View full text |Cite
|
Sign up to set email alerts
|

Salmon lice dispersion in a northern Norwegian fjord system and the impact of vertical movements

Abstract: The abundance and distribution of salmon lice Lepeophtheirus salmons originating from fish farms in a northern Norwegian fjord during the summer of 2010 was investigated by means of a numerical model, underpinned by field observations. In order to evaluate the robust-ness of the simulated distribution of the lice, we reran the simulation several times, changing the vertical responses of the lice to environmental cues such as light and turbulence, in addition to altering their vertical swimming velocity. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 63 publications
5
68
0
Order By: Relevance
“…In our study, we assumed that the infestation levels (abundance) found on the smolt are linked to the modeled salmon lice densities through a linear relationship. Our results indicate that this is a reasonable assumption and is also in accordance with results of Johnsen et al (2016). Although it has been shown that factors like the age of the lice, the water temperature, the current speed, the light conditions, turbulence, the water salinity, etc., influence the infestation process (Bricknell et al 2006, Samsing et al 2014), a complete understanding is still not established.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, we assumed that the infestation levels (abundance) found on the smolt are linked to the modeled salmon lice densities through a linear relationship. Our results indicate that this is a reasonable assumption and is also in accordance with results of Johnsen et al (2016). Although it has been shown that factors like the age of the lice, the water temperature, the current speed, the light conditions, turbulence, the water salinity, etc., influence the infestation process (Bricknell et al 2006, Samsing et al 2014), a complete understanding is still not established.…”
Section: Discussionsupporting
confidence: 92%
“…However, using a newer neighboring verification method (Ebert 2008), it was possible to demonstrate the potential of the model in the sense that the observed infestation levels are a possible projection from the model within a slight shift in space. The results are in accordance with the findings of Johnsen et al (2016), who tested the model system in a northern Norwegian fjord system (the Folda fjord system). The main finding in their paper was that the simulated densities of infective salmon lice varied in synchronization with lice infestations observed on wild sea trout.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Helland et al (2015) and Thorstad et al (2015) strongly suggest the transmission of lice from farm salmon to wild salmonids in systems where the fish occur in close vicinity. Future similar analyses should use available hydrodynamic-biological dispersal models , Johnsen et al 2016 to get a better estimate of the lice infestation pressure imposed by fish farms in different parts of the fjord systems along the Norwegian coast. …”
Section: Discussionmentioning
confidence: 99%
“…The growth of a sea lice population has an exponential nature (Frazer et al 2012) and is generally modelled as such (Costello 2006, Krkošek et al 2010, Frazer et al 2012. Several dispersion models have been developed which assume that the planktonic stages of the sea lice drift freely with prevailing currents close to the surface (Amundrud & Murray 2009, Adams et al 2012, Salama et al 2013, with recent works including vertical positioning as a response to environmental cues (Johnsen et al , 2016. Sea temperature is widely accepted as a basic factor influencing the growth rate of sea lice populations, as the generation time decreases with increasing temperature (Tully 1992, Heuch et al 2000.…”
Section: Introductionmentioning
confidence: 99%